The Relationship Between Diet and the Incidence of Anemia in Boarding School Children - Alvita Devi; Niluh Arwati (Westscience Press, 2024)
This study aims to investigate the relationship between dietary patterns and the incidence of anemia among female students living in dormitories at Bina Mandiri University, Gorontalo. Anemia is a common health issue, particularly in developing countries, with a high prevalence among women of reproductive age. This research is motivated by the high prevalence of anemia among young women in Indonesia, including female students living in dormitories. Data were collected through questionnaires and hemoglobin tests among students of the Faculty of Science, Technology, and Health Sciences (FSTIK). Preliminary results indicate that out of 5 respondents, 3 were found to be anemic. Irregular eating habits and low iron intake through diet were identified as major risk factors for anemia. This study is expected to provide valuable information for improving nutritional knowledge, particularly in efforts to prevent anemia among female students. The findings of this research may also serve as a reference for future studies and the development of more effective nutrition education programs.